The Impact of Islamic Business Ethics on the Sustainable Competitive Advantage of SMEs: An Empirical Study - Riza Wahyu Rahmanda; Renatha Aprilia; Achmad Basofitrah; Abd Rohim; Abdul Qodir (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the impact of Islamic business ethics on the sustainable competitive advantage of small and medium enterprises (SMEs) in Lumajang Regency. The research is grounded in the argument that ethical business conduct is not merely a normative religious obligation, but also a strategic resource that can strengthen long-term business performance. Using a qualitative approach with a case study design, this study explores how the implementation of Islamic business ethics is reflected in everyday business practices and how it contributes to the sustainability of competitive advantage. Data were collected through in-depth interviews, observation, and documentation involving SME owners, employees, and customers. The data were analyzed using data condensation, data display, and conclusion drawing/verification. The findings show that Islamic business ethics, particularly honesty, trustworthiness, fairness, and responsibility, plays a significant role in building customer trust, strengthening loyalty, enhancing business reputation, and supporting long-term relationships with consumers. These elements collectively form an intangible basis for sustainable competitive advantage. The study also reveals that ethical values are operationalized through simple but consistent practices, such as transparent pricing, truthful product information, fair service, and responsible complaint handling. Theoretically, this study contributes to the literature by positioning Islamic business ethics as a strategic intangible resource in explaining sustainable competitive advantage. Practically, the findings suggest that SME development should integrate ethical capacity alongside technical and economic strengthening. This study highlights the importance of value-based business practices in enhancing the resilience and sustainability of SMEs in a competitive market environment.